Predictive Values of Systemic Immune-Inflammation Index in New-Onset Atrial Fibrillation Following Coronary Artery Bypass Grafting - Yilmaz,Yucel (2022)
ABSTRACT Introduction: We investigated the relationship between the newly-defined systemic immune-inflammation index and the new-onset atrial fibrillation in patients undergoing coronary artery bypass grafting. Method: This study included 392 patients who underwent coronary artery bypass grafting. We divided the participants into two groups as those with and without new-onset atrial fibrillation. Prior to coronary artery bypass grafting, we evaluated blood samples, including systemic immune-inflammation index, and other laboratory parameters of the patients. We formulized the systemic immune-inflammation index score as platelet × neutrophil/lymphocyte counts. Results: The findings revealed that new-onset atrial fibrillation occurred in 80 (20.4%) of 392 patients during follow-ups. Such patients had higher systemic immune-inflammation index, neutrophil/lymphocyte ratio, and C-reactive protein levels than those who did not develop new-onset atrial fibrillation (P<0.001, P<0.001, P=0.010, respectively). In receiver operating characteristic curve analysis, systemic immune-inflammation index levels > 712.8 predicted new-onset atrial fibrillation with a sensitivity of 85% and a specificity of 61.2% (area under the curve: 0.781, 95% confidence interval: 0.727-0.835; P<0.001). Conclusion: Overall, systemic immune-inflammation index, a novel inflammatory marker, may be used as a decisive marker to predict the development of atrial fibrillation following coronary artery bypass grafting.